2005
DOI: 10.1152/ajpheart.00991.2004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between myocardial malate/aspartate shuttle activity and EAAT1 protein expression in hyper- and hypothyroidism

Abstract: . Correlation between myocardial malate/aspartate shuttle activity and EAAT1 protein expression in hyper-and hypothyroidism. Am J Physiol Heart Circ Physiol 288: H2521-H2526, 2005. First published December 22, 2004; doi:10.1152/ajpheart.00991.2004.-In the heart, elevated thyroid hormone leads to upregulation of metabolic pathways associated with energy production and development of hypertrophy. The malate/aspartate shuttle, which transfers cytosolicreducing equivalents into the cardiac mitochondria, is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
5
20
0
1
Order By: Relevance
“…T 3 promotes expression of important proteins involved in both glucose and lipid metabolism that may influence insulin secretion. In particular, carnitine palmitoyl transferase 1 (CPT-1) expression and activity (35,36), mitochondrial glycerol-3-phosphate dehydrogenase (mGPDH) activity (37), and levels of excitatory amino acid transporter type 1 (EAAT1) mRNA and protein (38) are increased by TH. EAAT1 and mGPDH are key components of the NADH shuttles which are essential for coupling glycolysis with mitochondrial ATP generation and triggering glucose-induced insulin secretion (39).…”
Section: Discussionmentioning
confidence: 99%
“…T 3 promotes expression of important proteins involved in both glucose and lipid metabolism that may influence insulin secretion. In particular, carnitine palmitoyl transferase 1 (CPT-1) expression and activity (35,36), mitochondrial glycerol-3-phosphate dehydrogenase (mGPDH) activity (37), and levels of excitatory amino acid transporter type 1 (EAAT1) mRNA and protein (38) are increased by TH. EAAT1 and mGPDH are key components of the NADH shuttles which are essential for coupling glycolysis with mitochondrial ATP generation and triggering glucose-induced insulin secretion (39).…”
Section: Discussionmentioning
confidence: 99%
“…The malate/aspartate as well as α-glycerophosphate shuttles show existence of sufficient capacity in cardiac mitochondria to accommodate increased shuttle flux even in hypertrophied myocardium that becomes more glycolytically active (RUPERT et al, 2000). However, elevated thyroid hormone leads to upregulation of metabolic pathways associated with energy production and development of heart hypertrophy, as observed by RALPHE et al (2005). Expression of excitatory amino acid transporter type 1 (EAAT1) mRNA and protein that functions as a glutamate carrier in the malate/aspartate shuttle was increased nearly threefold in T3-treated animals, whereas expression of aralar1 and citrin (both cardiac mitochondrial aspartate-glutamate transporters) mRNA and protein levels remain decreased and unchanged, respectively.…”
Section: Developmental Aspects Of Mdh Action and Functionsmentioning
confidence: 95%
“…However, the role of each isoform in MAS function remains unknown. Recent reports have suggested that the AGCs are only one of the possible players in the heart malate-aspartate shuttle at the step of glutamate uptake in mitochondria, and that the EAAT1, a plasma membrane glutamate carrier from brain, is localized to heart mitochondria and functions as a glutamate carrier within MAS (40,41). Therefore, it is necessary to clarify the contribution and role of each of the two AGC isoforms to understand MAS function in heart.…”
Section: Ef-hands In Citrin Andmentioning
confidence: 99%
“…Moreover, recent reports have introduced added complexity to heart MAS activity. Ralphe et al (40,41) have proposed that an isoform of the excitatory amino acid transporter type 1 (EAAT1) is present in heart mitochondria where it acts as a glutamate carrier within MAS and is responsible for the up-regulation of MAS by thyroid hormone.…”
mentioning
confidence: 99%